P14.14 Adjuvant treatment versus initial observation in newly diagnosed WHO grade II and grade III oligodendroglioma: real-life data from two academic, tertiary care centers in Austria. (9th September 2021) - Mair, M J; Leibetseder, A; Wöhrer, A; Widhalm, G; Dieckmann, K; Aichholzer, M; Weis, S; von Oertzen, T; Pichler, J; Preusser, M; Berghoff, A S
Abstract: BACKGROUND: Oligodendrogliomas are rare, slow-growing brain tumors with a survival prognosis of >10 years. Although adjuvant radio-chemotherapy has been shown to prolong survival, aggressive treatment comes at the cost of increased toxicity. Systematic data on the optimal timing of adjuvant treatment in oligodendroglioma are lacking. MATERIAL AND METHODS: Patients treated for a newly diagnosed IDH-mutated, 1p/19q-codeleted oligodendroglioma (WHO grades II/III) in 2000 - 2018 at the Medical University of Vienna or the Kepler University Hospital Linz (Austria) were included in this retrospective study. Adjuvant treatment was defined as radiotherapy (RT), chemotherapy (CHT) or radio-chemotherapy (R-CHT) within 6 months after resection in the absence of progression. "Wait and see" was defined as regular follow up with magnetic resonance imaging and treatment at progression. RESULTS: 185 patients were identified, comprising 123/185 (66.5%) WHO grade II and 62/185 (33.5%) WHO grade III oligodendrogliomas. Median age at diagnosis was 42 years (range: 20–82). Gross total resection (GTR) could be achieved in 77/178 (42.3%) evaluable patients. Adjuvant treatment was applied in 63/185 (38.2%) patients, of whom 43/63 (68.3%) underwent R-CHT, 9/63 (14.3%) CHT only and 11/63 (17.5%) RT only. 43/52 (82.7%) received temozolomide-based treatment, 1/52 (1.9%) procarbazine, lomustine and vincristine (PCV), 1/52 dacarbazine/fotemustine and in 7/52 (13.5%) patients, no data on used regimens was available. Adjuvant treatment was more frequently applied in WHO grade 3 tumors (p<0.001), while there was no association of adjuvant treatment with extent of resection (p=0.24). Patients after GTR who underwent adjuvant therapy presented with longer progression-free survival (PFS) compared to patients initially managed with observation (median: 150 months, 95%CI: 100 - not reached (n.r.) vs. median: 101 months, 95%CI: 73.2–115; p=0.053). In non-GTR tumors, patients with adjuvant therapy presented with a significantly longer median PFS of 107.5 months (95%CI: 62.8-n.r.) as compared to patients initially managed with observation (45.3 months, 95%CI: 41.2–78.8; p=0.025). CONCLUSION: The application of adjuvant therapy was associated with favorable PFS in patients who underwent resection of newly diagnosed oligodendroglioma in this retrospective study. Prospective clinical trials should investigate the risks and benefits of adjuvant treatment versus initial observation in patients with oligodendroglioma.